Solitary intraspinal juvenile xanthogranuloma in an infant - Shenoy, Asha; Singhal, Shruti; Shinde, Sweety (Asian Journal of Neurosurgery, 2018)
Juvenile xanthogranuloma (JXG) is a benign, non-Langerhans cell histiocytic proliferative disorder. We report a case of solitary JXG in an infant presenting as an intraspinal mass. Awareness of this mode of presentation is very important as subsequent prognosis differs from other tumors at the same location. JXG is a self-limiting dermatologic disorder usually occurring in first two decades of life. On rare occasion, it has been reported at extra-cutaneous sites such as central nervous system (CNS), eyes, liver, spleen, lungs and kidneys, and in other age groups. Isolated CNS involvement is extremely rare, especially in the spinal cord.
Keywords: Infant; intraspinal; juvenile xanthogranuloma